Asymmetric relationship between oil price and exchange rate: The case of Romania - Taşar, İzzet (My University, 2018)
The fragile structure of the global economy in the last decades makes it necessary for policy makers to have consistent predictions on the future values of the commodities and assets and also exchange rates. The fact that it is still the biggest source of energy, oil, has a crucial importance for the real economy and even financial markets. In this study, the relation of the real oil price and the real exchange rate in Romania will be investigated for the period of 2004:4 to 2014:10 using monthly data. Results in the tests suggest that Romania should consider the real oil price and real exchange rate causality due to the fact that there is a significant causality between the variables.

Global ekonomi sözlüğünde kırılganlık terimi sıkça karşılaşılan bir terim olagelmiştir. Bu da politika yapıcılar için önemli bir husustur. Enerji üretim için çok önemli bir girdi konumundadır ve bu girdi hala büyük ölçüde petrolden karşılanmaktadır. Bu çalışmada petrol fiyatları ve döviz kuru ilişkisi Romanya için irdelenmiştir. Bu çalışmanın veri aralığı 2004:4 ve 2014:10 tarih aralığındadır. Araştırmanın sonucu Romanya için petrol fiyatları ve döviz kuru arasında anlamlı bir ilişiki olduğunu göstermektedir.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Oil prices; Exchange rate; Romania; Asymmetric causality; Petrol fiyatları; Döviz kuru; Romanya; Asimetrik nedensellik